Digital Mangatoon to Born Out New Peace in English Classroom - Muthmainnah, Muthmainnah; J, Vargheese K; Ibna Seraj, Prodhan Mahbub; Darmawati, Besse; Asrifan, Andi (Universitas Siliwangi, 2022)
Digital comics are proven to be an effective learning tool for both teachers and students. At the university level, this study was set out to find the views of second-semester students on the use of Mangatoon digital comics in reading instruction. A quantitative study was performed, involving second-semester students at the Universitas of Al Asyariah Mandar (n=30). This study found, that on average, students find Mangatoon helpful in assisting them in reading since it has practical features preserving their motivation. Based on the student’s perception, the reading material presented in Mangatoon is easily understood, hence improvement in their reading skills can be maximised. Keywords: Digital Comic; Reading; ELT; and Pedagogical Innovation.